Stainless steel prestressed stayed columns. (13th September 2017) - Pichal, Radek; Machacek, Josef
ABSTRACT: Behavior of stainless steel prestressed stayed columns with a central crossarm is investigated numerically in 3D, following 3 tests of a reasonable size. The paper discusses previous analyses concerning critical loading and strength capacity with respect to influence of geometrical and material properties, prestressing and boundary conditions. Critical buckling loads and post‐buckling paths with regards to 2D and 3D GMNIA (geometrically and materially nonlinear analysis with imperfections) are demonstrated using ANSYS software. The buckling of the main column in 3D is shown, resulting into deflection in between the arms of the central crossarm, while the value of critical loading is rather unaffected in comparison with 2D analysis. Other results cover influence of the imperfection level with both symmetrical and antisymmetrical imperfection mode, boundary conditions at central crossarm (fixed or sliding stays) and nonlinear stainless steel material.